Wiring the writing center - Hobson, Eric (UPCC book collections on Project MUSE., 1998)
As computers have brought important developments to composition studies, writing centers have found themselves creating and improvising applications for their own work and often for the writing programs and institutions in which they live. Online tutorials, websites with an array of downloadable resources for students, scheduling and email possibilities--all of these are becoming common-place among writing centers across the country. However, in spite of impressive work by individual centers, exchange on these topics between and among writing centers has been sporadic. As more writing centers.